The Complexity and Diversity Methods of Legal Discovery in Islam: In the Perspective Ulama of Mazhab al-Arba'ah - Yazid, Afthon; Sugitanata, Arif (Kawanua International Journal of Multicultural Studies, 2023)
This article aims to detail the development of the method of finding sources of Islamic law concerning the perspectives of the scholars of the madhhab al-arba'ah, and explore its advantages and disadvantages based on the findings gathered. The research adopts a literature-based approach, a research method that relies on literature as the main source of information. Primary data sources are obtained from classical works, books, journals, and other related references related to the method of finding sources of Islamic law, especially in the perspective of the ulama mazhab al-arba'ah. Researchers use a qualitative approach with analytical descriptive methods to analyse primary data. The results show that the schools of Islamic law, such as Hanafi, Maliki, Shafi'i, and Hambali, show differences in the method of legal discovery and its implementation. Each school has distinctive characteristics based on its origin's sociocultural and political context. The thoughts of the leading figures in developing the science of usul fiqh, such as Abu Hanifah, Imam Malik, Imam Shafi'i, and Imam Ahmad, reflect the differences in ijtihad and law-making methods in these schools. Thus, this article provides an overview of the complexity and diversity of legal discovery methods in the Islamic context, illustrates the evolution of legal thought over time, and highlights the different approaches among the schools of Islamic law.